Prostate cancer survivorship essentials framework: guidelines for practitioners. Issue Volume 128:Issue Supplement 3(2021) (18th August 2020) - Dunn, Jeff; Green, Anna; Ralph, Nicholas; Newton, Robert U.; Kneebone, Andrew; Frydenberg, Mark; Chambers, Suzanne K.
Abstract : Objective: To develop contemporary and inclusive prostate cancer survivorship guidelines for the Australian setting. Participants and Methods: A four‐round iterative policy Delphi was used, with a 47‐member expert panel that included leaders from key Australian and New Zealand clinical and community groups and consumers from diverse backgrounds, including LGBTQIA people and those from regional, rural and urban settings. The first three rounds were undertaken using an online survey (94–96% response) followed by a fourth final face‐to‐face panel meeting. Descriptors for men's current prostate cancer survivorship experience were generated, along with survivorship elements that were assessed for importance and feasibility. From these, survivorship domains were generated for consideration. Results: Six key descriptors for men's current prostate cancer survivorship experience that emerged were: dealing with side effects; challenging; medically focused; uncoordinated; unmet needs; and anxious. In all, 26 survivorship elements were identified within six domains: health promotion and advocacy; shared management; vigilance; personal agency; care coordination; and evidence‐based survivorship interventions. Consensus was high for all domains as being essential. All elements were rated high on importance but consensus was mixed for feasibility. Seven priorities were derived for immediate action. Conclusion: The policy Delphi allowed a uniquely inclusive expert clinical and community group to develop prostate cancer survivorship domains that extend beyond traditional healthcare parameters. These domains provide guidance for policymakers, clinicians, community and consumers on what is essential for step change in prostate cancer survivorship outcomes.